Fostering elementary school children's public speaking skills: A randomized controlled trial. (June 2018) - Herbein, Evelin; Golle, Jessika; Tibus, Maike; Schiefer, Julia; Trautwein, Ulrich; Zettler, Ingo
Abstract: Mastering public speaking is a competence which is already required in elementary school. Surprisingly, however, systematic research on the promotion of public speaking competence among elementary school children is scarce. In order to address this gap, we developed and evaluated a public speaking training for elementary school children. The training, an extracurricular enrichment program, consisted of 12 units covering speech anxiety, nonverbal communication, and comprehensibility. A randomized controlled trial with repeated measures ( N = 65 elementary school children) was used to investigate the training effects on public speaking skills and speech anxiety. The dependent variables were assessed via self-ratings (extent of public speaking skills, speech anxiety) and video ratings of a public speech (appropriateness of public speaking skills). Findings revealed positive training effects on public speaking skills overall: Participating in the training elicited more appropriate speeches in terms of nonverbal and organizational skills but did not influence speech anxiety. Highlights: A speech training was developed to foster 3rd & 4th graders' public speaking skills. Training effects were evaluated via a randomized controlled trial. Training effects were assessed by self-reports and external video ratings. Participating in the training resulted in more appropriate public speaking skills. No effects on speech anxiety were found.